Pedagogi Shalom: Analisis Kristis Terhadap Pedagogi Kritis Henry A. Giroux dan Relevansinya Bagi Pendidikan Kristen di Indonesia - Dami, Zummy Anselmus (Jurnal Filsafat "WISDOM", 2019)
This paper is a critical analysis towardcritical pedagogy in education using the concept of the pedagogy of shalom. Critical analysis is undertakennot to imply that critical pedagogy as formulated by Giroux is a wrong conceptbut this paper aims to recover the fragility and refining that has not been perfect through the values of the divine pedagogy of shalom. Critical pedagogy and shalom pedagogy struggle to question and challenge the mindset and lifestyle underlying the pedagogy of neoliberal that emphasisses market fundamentalism and ultimately create oppression, social injustice and revokedemocracy. Based on this orientation, pedagogy of shalomis introduced to reinforce the foundations and basic theories of critical pedagogy so it doesnnot merely align to activism, withoutreconciliation and to avoid arrogant of social movements and the criticism to power but without theestablishmentof love. The main objective is to achieve social and political changes to thebetter so that public can live injust, free, prosperous and equitablesociety.This article further seeks possibility to apply the concept of the pedagogy of shalom in the context of Christian education in Indonesia